BPD's Role in Village Development Planning - Subiyanto; Agustina, Isna Fitria (Indonesian Journal of Cultural and Community Development, 2024)
General Background in this context, the Village Consultative Body (BPD) serves as a key institution supporting the development planning process. Specific Background however, understanding the specific role of the BPD in development remains limited. Knowledge Gap this research aims to analyze and describe the role of the BPD in village development planning. Aims data collection methods used include observation, interviews, and documentation, with data analysis through collection, reduction, presentation, and verification. Results findings show that the BPD plays a crucial role in formulating and agreeing on village regulations and as a channel for community aspirations. An adaptive organizational structure of the BPD and the involvement of community elements make this process more efficient. Success the assessment of the BPD’s role in village development received positive responses from the community. Implications however, challenges remain regarding the passivity of BPD members, which can affect the optimization of village regulation formulation. This study highlights the importance of strengthening the BPD's capacity to be more responsive to community needs. Highlights: The BPD is essential for channeling community aspirations into development plans. Positive community feedback indicates effective BPD involvement in village governance. Challenges include passive member engagement, hindering optimal regulation processing. Keywords: Village Consultative Body, Development Planning, Community Aspirations, Village Regulations, Organizational Structure